Ganobuster: Novel, Easy, and Clean Basal Stem Rot Detection System of the Palm Oil Trunk - Ali Yeon, Mohd Shakaff, Prof. Dr. (Principal); Mohd Noor, Ahmad, Prof. Dr.; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr.; Abdul Hamid, Adom, Prof. Madya Dr.; Abu Hassan, Abdullah; Farizul Hafiz, Kasim; Ahmad Faizal; Shah Fenner Khan; Anas, Mohd Noor; Norahim, Ibrahim; Noor Hasyierah, Mohd Salleh; Marni Azira, Markom (INPEX, 2010)
Prof. Dr. Ali Yeon Mohd Shakaff and his team won silver for Ganobuster: Novel, Easy, and Clean Basal Stem Rot Detection System of the Palm Oil Trunk at INPEX USA, 6th - 9th June 2007 at Pittsburgh, PA USA.